Role of Fibroblast Growth Factor 10 in Mesenchymal Cell Differentiation During Lung Development and Disease - Wu, Jin; Chu, Xuran; Chen, Chengshui; Bellusci, Saverio (Frontiers in Genetics, 2018)
Fibroblast growth factor 10 (Fgf10) regulates mesenchymal cell differentiation in the lung both during development and in disease conditions. Different mesenchymal cell types exist in the developing lung mesenchyme. Lineage tracing in vivo was used to characterize these cells during development and disease. Fgf10-positive cells in the early lung mesenchyme differentiate into multiple lineages including smooth muscle cells, lipofibroblasts (LIFs) as well as cells, which still remain to be characterized. Breaking the paradigm that in the lung, Fgf10 acts only in the epithelium, we reported that Fgf10 acts on LIF progenitors to control their differentiation.. In this review, we are summarizing the mechanisms controlling LIF formation during development. Alveolar myofibroblast (MYF), which are critical for the process of alveologenesis (the last phase of lung development) are also dependent for their formation on Fgf10 signaling. Forced Fgf activation in the embryonic lung mesenchyme, due to an ectopic mesenchymal Fgf10-Fgfr2b autocrine loop, leads to the absence of alveolar MYF formation at birth. Characterization of the alveolar MYFs in the developing lung using lineage tracing was recently carried out. We found that these cells are enriched in Fgf10 expression as well as in genes involved in Wnt and Hedgehog signaling. In contrast to the alveolar MYF, which are required for normal development, another type of MYF associated with pathogenic processes and called "activated" MYF are highly present in the fibrotic foci of patients with idiopathic pulmonary fibrosis. These pathological cells express high level of extracellular matrix proteins and are causative for the disease. We have recently reported a LIF to activated MYF reversible transdifferentiation switch during fibrosis formation and resolution. Activation of PPARγ signaling in the activated MYF antagonizes TGFb1-Mediated fibrogenic response. The therapeutic function of recombinant FGF10, a known activator of PPARγ signaling in the mesenchyme, is therefore very promising.